PUZZLE GAME APPLICATIONS IN CONCENTRATION AND NETWORK USING MICROSOFT VISUAL BASIC SWISHMAX 6 - Mohammad Renandi Irzani; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Computers can give the impression of a separate votes in play. One reason is becausethe support for communication between a computer device that allows a game can beplayed simultaneously though at different places. Unfortunately to make a gameapplication with a common language feels a bit difficult. But with the presence ofMacromedia Flash applications, make an application to the game with attractivegraphics and animation easier. Besides the output file from Macromedia Flashapplications can be integrated with the Visual Basic programming language so thatcan make an application which can communicate between computers and had anattractive app